2009
DOI: 10.1007/s10479-008-0501-4
|View full text |Cite
|
Sign up to set email alerts
|

Metaheuristics for the multi-objective FJSP with sequence-dependent set-up times, auxiliary resources and machine down time

Abstract: This paper investigates the application of particle swarm optimization (PSO) to the multi-objective flexible job shop scheduling problem with sequence-dependent set-up times, auxiliary resources and machine down time. To achieve this goal, alternative particle representations and problem mapping mechanisms were implemented within the PSO paradigm. This resulted in the development of four PSO-based heuristics. Benchmarking on real customer data indicated that using the priority-based representation resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The consumer wants to get the product delivered at required time and hence scheduling becomes a critical factor in meeting this demand [5] and plays a vital role in the operation of any manufacturing environment. The scheduling problem aims to formulate a processing order that can achieve a desired objective in an optimal manner which can be total time required for completing all operations, maximum lateness, maximum earliness, and so on.…”
Section: Schedulingmentioning
confidence: 99%
“…The consumer wants to get the product delivered at required time and hence scheduling becomes a critical factor in meeting this demand [5] and plays a vital role in the operation of any manufacturing environment. The scheduling problem aims to formulate a processing order that can achieve a desired objective in an optimal manner which can be total time required for completing all operations, maximum lateness, maximum earliness, and so on.…”
Section: Schedulingmentioning
confidence: 99%
“…Rahmati et al [67] developed non-dominated sorting of EA and non dominated ranking EA for multi-objective PFOSP and he proposed new multi-objective Pareto-based modules and a new measure for the multi-objective evaluation. [42] 2002 FOSP EA + AL Baykasoglu et al [7] 2004 FOSP TS + PDR Xia and Wu [79] 2005 FOSP PSO + SA Gao et al [26] 2006 FOSP EA Gao et al [27] 2007 FOSP EA + BSP Zribi et al [89] 2007 FOSP EA + BBA + LS Gao et al [28] 2008 FOSP EA + VNS Tay and Ho [75] 2008 FOSP EA + PDR Wang et al [76] 2008 FOSP FBS + PDR Zhang et al [87] 2009 FOSP PSO + TS Li et al [50] 2010 FOSP EA + VNS Frutos et al [25] 2010 FOSP EA + SA Wang et al [77] 2010 FOSP EA + AIS Gao et al [30] 2010 FOSP EA + AIS Grobler et al [35] 2010 FOSP PSO + PDR Li et al [48] 2010 FOSP TS + VNS Moradi et al [58] 2011 FOSP EA + PDR Moslehi and Mahnam [59] 2011 FOSP PSO + LS Li et al [49] 2011 FOSP PSO Li et al [47] 2011 FOSP PSO Rajkumar et al [68] 2011 FOSP GRASP Chiang and Lin [17] 2013 FOSP EA Rahmati et al [67] 2013 FOSP Gas Shao et al [72] 2013 FOSP PSO + SA Gao et al [29] 2014 FOSP HSA + LS Jia and Hu [41] 2014 FOSP TS Karthikeyan et al [45] 2014 FOSP DFA + LS Li et al [51] 2014 FOSP PSO + TS Rohaninejad et al [69] 2015 FOSP EA Yuan and Xu [84] 2015 FOSP EA + LS Rohaninejad et al [69] proposed a nonlinear IP model and also the hybridized EA with meta-heuristic, which is a multi-attribute decision making method, for multi-objective PFOSP with machines capacity constraints. The computational results are obtained by well-known multi objective algorithms from the literature showed that the proposed algorithm to obtain throughout better performance, especially in the closeness of the solutions result to the Pareto optimal front.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xia and Wu [79] combined simulated annealing with particle swarm optimization to omit, being trapped in a local optimum for multi-objective PFOSP. Grobler et al [35] developed four particle swarm optimization similar to meta-heuristic approach for multi-objective PFOSP with sequence-dependent setup times. The priority-based particle swarm optimization algorithm was executed for the best performance and respect to the quality of a solution and their computational complexity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xia and Wu [62] combined simulated annealing with particle swarm optimization for a multi-objective FJSP. Grobler et al [63] applied four particle swarm optimization-based heuristic approaches to the multi-objective FJSP with sequence-dependent setup times. The priority-based particle swarm optimization algorithm has the best performance in terms of the quality of the solution and the computational complexity.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%